A customized 3D bio-macroporous cryogels for efficient and selective gold extraction - Haleem, Abdul; Pan, Yang; Wu, Fan; Ullah, Mohib; Chen, Shengqi; Li, Hao; Pan, Jianming (Separation and purification technology, 2024)
•Construction of 3D bio-macroporous cryogels via UV-radiation.•The developed system has the ability for efficient and selective gold extraction.•The adsorption capacity measured in the experiment for gold was 613.27 mg g−1 (C0 = 1200 mg g−1, 308 K, pH = 3)•The designed bio-macroporous cryogel has better thermal stability and shelf-life. The swift and efficient extraction of gold from electronic wastes carries significant economic and environmental benefits. In the present work, chitosan and keratin were modified with vinyl pyrrolidone via grafting cryopolymerization used UV-irradiation for efficient Au(III) removal from actual electronic waste solution. The rapidly attaining adsorption equilibrium for Au(III) within just 4 h can be attributed to the biosorbent macroporous nature. Under ideal conditions (C0 = 1200 mg g−1, 308 K and pH 3), the Freundlich model exhibited superior fitting, showcasing the biosorbent's remarkable adsorption capacity for Au(III) at an impressive amount of 613.27 mg g−1. An Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES, Varian) was implemented to measure the adsorption of Au(III) and other coexisting ions. Additionally, the biosorbent displayed enhanced thermal stability and a prolonged shelf-life, indicating its potential for use in challenging environmental conditions. In addition to its stability, the material maintained its Au(III) adsorption efficiency after four consecutive usage cycles. In addition, it exhibited the capacity to specifically adsorb Au(III) from leaching solutions of electronic waste, resulting in a recovery rate of 89.2 %. The presence of amino (–NH2) and sulfide (-S-S-) functional groups on the biosorbent played a pivotal role in capturing Au(III) ions through electrostatic and chelation mechanisms. The presence of sulfide linkage and amino (–NH2) functionality, a major component of keratin is a pristine factor in this study, particularly well-suited for Au(III) extraction. The crosslinked biosorbent introduced random pores due to its random cooling process, enabling efficient diffusion and more significant Au(III) retention than traditional gels. In addition to its capacity for recovering precious metals from electronic waste, this biosorbent is a cost-effective solution with promising applications in environmental remediation and wastewater treatment.